PROBLEM OF ONLINE LEARNING AMONG STUDENTS UUM: TECHNOLOGY ACCESS, ASSESSMENT, AND SELF-EFFICACY - Aini Firhani Abdul Rasid; Rosini Nawang Mustapen (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Using online learning is getting relevant in education perspective. In order embrace online learning effectiveness, university should provide proper suitable tools towards more efficient for online learning implementation. This aims for this paper is to understand students’ problems during using online learning that provided by the university. The paper used a qualitative approach through unstructured interviews from the student’s perspective. Ten students from different routes of inasis were interviewed. Three themes of online learning problem were selected: technology access, assessment, and self-efficacy by using thematic analysis. Based on the analysis, most of the respondents admitted they are having problem with wi-fi networks and coverage, and it makes uncomfortable to study through online. This study also highlighted, the managements should provide strategy how to minimize fraudulent issue during completing task and online examinations. An in-depth understanding from the voices of students was essential for further action and improvement in fostering the online learning effectiveness in higher educations. Thus, study is offering valuable insight for understanding the real experiences from students’ perspective for online learning in higher education.